Contamination of the terms «educational space» and «learning environment» in the modern scientific and pedagogical discourse (Pedagogy of Higher and Secondary Education, 2013)
Doroninа T. A. Contamination of the terms «educational space» and «learning environment» in the modern scientific and pedagogical discourse.In the article problems of Ukrainian education space in the context of integration processes are analyzed. The article gives a review of theoretical problems connected with the category of «educational space» and «educational environment». The article presents new approaches to understanding the educational environment, educational space.
Keywords: the integration processes; educational space; educational environment